Microsatellite Instability in Sacral Chordoma - KLINGLER, LANCE (J Surg Oncol, 2000)
BACKGROUND AND OBJECTIVES: Microsatellite instability (MIN) is an indirect marker of globally defective DNA mismatch repair in the neoplastic cells of cancer patients. Chordomas are rare, primary skeletal malignancies for which few characteristic molecular genetic markers have been identified. Is MIN demonstratable in chordoma? METHODS: We evaluated sacral chordomas from 12 patients with sacral chordomas for the presence of MIN at 9 different genetic loci from chromosomes 1p, 5q, 7q, 9p, 11p, 12p, 13q, 17p, and 18q. Cells were scraped from glass slides so that tumor and control DNA could be isolated and then amplified by polymerase chain reaction (PCR). Heterozygosity indices were ≥ 0.70. RESULTS: Six patients (50%) demonstrated MIN for at least 1 locus, and 2 patients demonstrated loss of heterozygosity (LOH) for at least 1 locus. Only 1 individual’s chordoma manifested microsatellite instability (MIN) and loss of heterozygosity (LOH). Another patient manifested no MIN but LOH at 9p and 18q. Interestingly, this individual had the most aggressive clinical cancer course, presenting with lymph node metastasis and succumbing to widespread metastatic disease. CONCLUSIONS: Chordomas can be added to the list of malignancies demonstrating MIN. LOH may prove to portend a worse prognosis than MIN when more tumors are examined.